Impact of Affiliate Marketing in e Business on Consumer Buying Behaviour (International Journal of Food and Nutritional Sciences, 2022)
This research paper explores the influence of affiliate marketing on consumers' decision-making process in the e-commerce industry and its implications for consumer behaviour. The study aims to contribute to the existing body of knowledge by investigating the impact of affiliate marketing on various aspects of consumer behaviour, including purchase decisions, trust, perception of product quality and value, online shopping experience, discovery of new products and brands, consideration of affiliate marketers' opinions, and perception of better deals and discounts. The study employed a one-sample t-test to analyse data collected from participants regarding their perceptions of affiliate marketing and its influence on their decision-making process. The results of the analysis revealed significant findings, indicating that affiliate marketing strongly influences consumers' purchase decisions and plays a vital role in shaping their perception of products. Participants expressed a high level of trust in products recommended through affiliate marketing, valued the information provided, and reported an enhanced online shopping experience. Moreover, affiliate marketing was found to impact consumers' perception of product quality and value, as well as their willingness to consider affiliate marketers' opinions and recommendations. The findings of this research have implications for businesses operating in the e-commerce industry, highlighting the importance of implementing effective affiliate marketing strategies to influence consumer behaviour and drive favourable outcomes. Transparency and ethical practices in affiliate marketing are also emphasized to build and maintain consumer trust.